Авиационные моментные двигатели - Столов Л. И. Лев Израилевич; Зыков Б. Н. Борис Николаевич; Афанасьев А. Ю. Анатолий Юрьевич; Галеев Ш. С. (Москва, Машиностроение, 1979)
Авторы указаны на обороте титульного листа